Fashion or Function? The Use of Silver in Seventeenth-Century Irish Society. Issue 1 (December 2021) - Cunningham, Jessica
What was more important to consumers in seventeenth-century Ireland: the fashion or the function of their silver? This article disentangles the multiple and complex motivations informing the robust acquisition and consumption by individuals and institutions of a wide-ranging assortment of silverwares. Using the body of extant plate and a large array of documentary sources, this article poses and addresses several questions that have hitherto received little or no attention in the literature: How was silver used in seventeenth-century Ireland? Can we dismiss or prioritise the use value of items ostensibly acquired for symbolic, ceremonial or commemorative purposes? Did design and decoration matter? And, if so, how did this impact on value and utility? By answering these questions, this article evaluates plate as a material simultaneously facilitating functional purposes and expressing taste. This article uses these conclusions to generate a greater understanding of early modern Irish consumer society and the role of silver within this society.